2017
DOI: 10.1016/j.jhep.2017.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma decreases the chance of successful hepatitis C virus therapy with direct-acting antivirals

Abstract: Background & Aims The approval of all-oral direct-acting antiviral (DAA) regimens for the treatment of hepatitis C virus (HCV) has led to the expansion of therapy to include patients with cirrhosis who have hepatocellular carcinoma (HCC). Data on the use of DAAs in HCV+ patients with HCC is limited. The aim of this study was to assess the efficacy of all-oral-DAA regimens in HCV+ cirrhotic patients who have or had HCC compared to those without HCC. Methods A retrospective cohort study was conducted on all ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
147
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(166 citation statements)
references
References 16 publications
16
147
2
1
Order By: Relevance
“…Therefore, higher pre-treatment levels of NKG2D (as shown in Table 1 and Fig 2) could result from such imbalance of inflammatory cytokines from both immune cells or other hepatic non-parenchymal cells such as hepatic stellate cells, especially in highly fibrotic livers, like the cases in IFN − /DAA group of this current study, even if no HCC was clinically evident at the time point of start of IFN-free DAA administration. Recently, Prenner et al showed in a retrospective study that the existence of active HCC might reduce the rate to achieve SVR by IFN-free DAAs[37]. As we also showed in Table 1 that non-SVR correlated to early emergence of clinically evident HCC, pre-treatment existence of clinically undetectable HCC may be suggested as a causative factor for treatment failure.…”
Section: Discussionsupporting
confidence: 64%
“…Therefore, higher pre-treatment levels of NKG2D (as shown in Table 1 and Fig 2) could result from such imbalance of inflammatory cytokines from both immune cells or other hepatic non-parenchymal cells such as hepatic stellate cells, especially in highly fibrotic livers, like the cases in IFN − /DAA group of this current study, even if no HCC was clinically evident at the time point of start of IFN-free DAA administration. Recently, Prenner et al showed in a retrospective study that the existence of active HCC might reduce the rate to achieve SVR by IFN-free DAAs[37]. As we also showed in Table 1 that non-SVR correlated to early emergence of clinically evident HCC, pre-treatment existence of clinically undetectable HCC may be suggested as a causative factor for treatment failure.…”
Section: Discussionsupporting
confidence: 64%
“…NKG2D is a well known immunoreceptor with implications in activating the immune responses against both infected and transformed cells. The [48]. Similar results were confirmed by Prenner et al [47,49], who showed that the presence of active HCC had a negative impact on achieving SVR.…”
Section: Molecular Mechanisms Of Hcc Occurrence or Recurrence With Dasupporting
confidence: 73%
“…Eradicating hepatitis C infection results in numerous health benefits, including reduced rates of all‐cause mortality, cirrhosis, hepatic decompensation, and HCC . Successful treatment also confers improvement in extrahepatic manifestations of HCV disease, including cryoglobulinemic vasculitis and HCV‐related non‐Hodgkin lymphoma and other lymphoproliferative disorders, as well as improved productivity and quality of life .…”
Section: Universal Treatment Of Adults With Chronic Hepatitis C and Smentioning
confidence: 99%